THE The Influence Of Leadership Style And Work Motivation On The Performance Of Junior High School Teachers In Sentajo Raya District, Kuantan Singingi District - Yulianti, Meti; Makhdalena; Caska (Tadrib: Jurnal Pendidikan Agama Islam, 2023)
Education is an important part of the national development process which also determines the economic growth of a country. The teacher is one component that occupies a central and very strategic position in the education system. Therefore, to achieve good quality education, teacher performance is very necessary. Teacher performance is a determinant of the high and low quality of education. To improve the performance of a teacher, of course, something is needed, something that is often referred to as motivation. Motivation is closely related to ways of directing the power and potential of subordinates so that they can work productively and achieve predetermined goals. In addition, the factor that can affect teacher performance is the leadership style of the school principal. The leadership role of the principal determines the success of an educational institution. This study aims to determine the effect of leadership style and work motivation on the performance of junior high school teachers in Sentajo Raya District. This research uses quantitative research methods with descriptive and verification approaches. The teachers who were respondents in this study were 84 teachers in seven junior high schools in Sentajo Raya District. The data in this study were obtained by distributing questionnaires to junior high school teachers in Sentajo Raya District. Data collection was carried out offline, namely by distributing questionnaires directly to respondents because researchers could meet directly with respondents so that they could convince respondents about the seriousness of this research. Data analysis in this study used the Partial Least Square (PLS) approach with smart PLS 3.0 software. The results showed that leadership style and work motivation had a significant effect on teacher performance at junior high schools in Sentajo Raya District, Kuantan Singingi Regency.